Natural Products: Insights into Leishmaniasis Inflammatory Response. (11th October 2015) - Rodrigues, Igor A.; Mazotto, Ana Maria; Cardoso, Verônica; Alves, Renan L.; Amaral, Ana Claudia F.; Silva, Jefferson Rocha de Andrade; Pinheiro, Anderson S.; Vermelho, Alane B.
Abstract : Leishmaniasis is a vector-borne disease that affects several populations worldwide, against which there are no vaccines available and the chemotherapy is highly toxic. Depending on the species causing the infection, the disease is characterized by commitment of tissues, including the skin, mucous membranes, and internal organs. Despite the relevance of host inflammatory mediators on parasite burden control, Leishmania and host immune cells interaction may generate an exacerbated proinflammatory response that plays an important role in the development of leishmaniasis clinical manifestations. Plant-derived natural products have been recognized as bioactive agents with several properties, including anti-protozoal and anti-inflammatory activities. The present review focuses on the antileishmanial activity of plant-derived natural products that are able to modulate the inflammatory response in vitro and in vivo . The capability of crude extracts and some isolated substances in promoting an anti-inflammatory response during Leishmania infection may be used as part of an effective strategy to fight the disease.